The Characteristic of Measles Epidemic Process in Kyrgyz Republic - M. S. Niiazalieva; O. V. Tsvirkun; V. S. Toygombaeva; I. Sh. Aldjambaeva; G. S. Ishenapysova; R. A. Frolov; G. S. Dadanova (Эпидемиология и вакцинопрофилактика)
Relevance. In the Kyrgyz Republic, the measles and rubella elimination program has been implemented in accordance with the strategy of the World Health Organization (WHO) for 20 years, which uses a two-fold immunization tactic against measles at the age of 12 months and 6 years, which is complemented by clean-up campaigns. Despite the high coverage of vaccinations with both the first and second doses, there are epidemic rises in infection, reaching in 2018 (15.9), 2019 (36.4) and 2020 (11.2) per one hundred thousand population. In the years of recent epidemic ups, a high incidence among young children revealed. The epidemiological situation with measles that has developed in recent years has made it necessary to study the state of specific measles immunity in different age groups, to determine the vulnerable population group and assess the quality of vaccination work.The aim of the work: to assess the epidemic process of measles at the present stage and the state of specific immunity in the population of the Kyrgyz Republic to identify groups at high risk of infection.Materials and methods. In the course of the work, descriptive-evaluative and analytical epidemiological research methods are used. The materials are statistical reporting data on the incidence of measles from 1987 to 2020 and 568 blood serum samples taken from residents of Bishkek and Jalal-Abat region in the following indicator age groups: 1-4 years old n = 122; 5-9 years old n = 108; 10-14 years old n = 114; 15-19 years old n = 77; 20-29 years old n = 103; 30 years and older n = 44. The level of anti-measles antibodies is determined by enzymelinked immunosorbent assay (ELISA) using the VectorMeasles-IgG test system manufactured by VEKTOR BEST, Russia. The method of retrospective analysis of the incidence of measles in the Kyrgyz Republic in long-term dynamics, by age groups, according to vaccination history is used. The method of retrospective analysis of the incidence of measles in the Kyrgyz Republic in longterm dynamics, by age groups, according to vaccination history is used. The data obtained statistically processed using the Excel program. The critical level of significance is p = 0.05. Descriptive statistics – mean and standard error of the mean (data are presented as M ± m) for quantitative variables, for qualitative variables – determination of proportion.Results and Discussions. The introduction of specific prophylaxis of measles led to decrease the incidence of measles, 15 times on average, mortality also decreased, however, despite the effectiveness of vaccination, cyclical increases in infection persisted, seasonality in intra-annual dynamics, school-age children began to get sick more often. To change the situation, including in order eliminating primary postvaccination failures, in 1986 a second dose of vaccine introduced into the vaccination schedule for children 6 years old, which led to decrease the incidence to single case and in some years to the complete absence of measles cases. However, in 2018, the importation of measles from bordering countries led to an epidemic outbreak with the number of cases of 1004. The incidence rate increased from 0.1 in 2017 to 15.9 per 100 thousand population in 2018. At the subnational level, a clean-up campaign carried out among children aged two to five years. However, due to the lack of vaccine, the target group covered less than 50% and the increase in the incidence of measles in 2019 continued to 2377 people (36.4 per 100 thousand population). A slight decrease in the incidence of measles outlined in 2020, when 733 cases were registered. The highest percentage of cases is among children under one year old, 43.3% (2019) and 52.7% (2020), who are not vaccinated by age. In second place in importance is the age group of children from one to four years old, an extensive incidence rate is 29.5% (2019) and 39.3% (2020). The data of serological studies confirmed the formation of a high-risk group for measles infection among preschool children, where the proportion of seronegatives is 36%; this is probably due to not post-vaccination failures, but rather to a high proportion of children who are not vaccinated for various reasons. This hypothesis confirmed by the high percentage of unvaccinated children of this age in the structure of the sickindividuals. All this casts doubt on the official data on the coverage of children of this age with preventive vaccinations (95.7%) and indicates the accumulation of contingents susceptible to measles. The results of our research are consistent with the data obtained by other researchers.Conclusion. The analysis showed the need for regular monitoring of the organization of the vaccination work to control the reliable accounting of the child contingent needed to immunization, based on the population census, as well as to identify the validity of medical withdrawals. To prevent the growth of refusals from vaccinations, it is advisable to expand the forms of work with the population to develop commitment to vaccination. We believe that in combination, this will increase the real coverage of measles vaccinations for children, reduce the number of sources of infection and indirectly reduce the risk of infection in children of the first year of life.